2008
DOI: 10.1111/j.1532-5415.2007.01552.x
|View full text |Cite
|
Sign up to set email alerts
|

Medical Student Attitudes Toward Older People and Willingness to Consider a Career in Geriatric Medicine

Abstract: Attitudes toward older people were better in fourth-year than first-year medical students. A more-positive attitude toward older people increased the likelihood of considering a career in GM. An intensive 8-day course in GM had no significant effect on attitudes but increased the likelihood of fourth-year students considering a career in GM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
111
5
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(129 citation statements)
references
References 10 publications
9
111
5
4
Order By: Relevance
“…In studies conducted by Vefikuluçay (6), (24), and Güven et al (25), a significant difference was determined between the average total AAS score and the sub-scale scores with respect to the students grades. The negative attitudes of the fourth-grade students were lower than those of the first-grade students (6,18,20,21,(23)(24)(25). The fact that the average total AAS score was higher may be correlated with the fourth-grade students having positive attitudes toward the elderly, their working hours with the elderly being greater, and their adoption of the notion of individual equality in nursing practices.…”
Section: Discussionmentioning
confidence: 99%
“…In studies conducted by Vefikuluçay (6), (24), and Güven et al (25), a significant difference was determined between the average total AAS score and the sub-scale scores with respect to the students grades. The negative attitudes of the fourth-grade students were lower than those of the first-grade students (6,18,20,21,(23)(24)(25). The fact that the average total AAS score was higher may be correlated with the fourth-grade students having positive attitudes toward the elderly, their working hours with the elderly being greater, and their adoption of the notion of individual equality in nursing practices.…”
Section: Discussionmentioning
confidence: 99%
“…13,17,[19][20][21][22] As Hughes and colleagues found, students' comfort levels with the elderly probably increased as a result of interacting with geriatric patients during the course. 3 Study findings show that for most items, gender, age, race/ethnicity, marital status, having children, and type of upbringing (rural or not) were not related to the students' attitudes. Similarly, a previous study among pharmacy students found that all demographic factors except gender were not related to the students' attitudes.…”
Section: Discussionmentioning
confidence: 90%
“…23 In addition, several studies among medical and dental students did not find a relationship between demographic factors and attitudes. 3,15,17 The study had some limitations. First, this study included students from only 1 institution so the results may not be generalizable to other pharmacy students at other institutions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also suggested that special considerations should be given to the knowledge and attitudes of nursing educators with emphasis on the importance of gerontological nursing education in nursing curricula, with the focus on changing the attitudes of nursing students to gaining positive knowledge and clinical experiences in gerontological care. All of the above appear essential if students are to choose gerontological nursing (14)(15)(16)(17)(18) .…”
Section: Introductionmentioning
confidence: 99%